Pembinaan Penggunaan Enzim A-Amilase Dan B-Glukoamilase pada Proses Pembuatan Pati Sagu Menjadi Gula Sagu pada Petani Sagu di Kabupaten Kepulauan Meranti - Meldra, Delia; Mardiansyah, Yopy; Azharman, Zefri (PUAN INDONESIA, 2024)
The high national demand for sugar makes Indonesia very dependent on imports of cane sugar. Alternative products are urgently needed to reduce dependence on imported cane sugar, and one product that has potential is sago sugar. Currently, sago sugar is starting to be developed, one of which is in Sungai Tohor Village, Tebing Tinggi Timur District, Meranti Islands Regency. The aim of the service is to identify the process of processing sago into sago sugar, provide knowledge about the enzymes ?-amylase and ?-glucoamylase and their applications, provide enzyme packages that act as a binder as one of the factors in making sugar, reactivate production, teach e-commerce promotion, and recommend suggestions regarding the development of sago sugar products. The method or approach used in this activity is a participatory approach. This approach is a practice of communicative, transactive, advocative and collaborative planning theories. In carrying out this service, it was carried out well, from the delivery of materials, procurement of enzyme packages, manufacturing processes, and making attractive sago sugar packaging. Delivery of service material is done online with several constraints of funds, time, distance, energy, and conditions that do not allow service members to go back and forth in one day or stay overnight in the area, and considering that the process of making sago sugar will also take a long time. The enzyme package is the biggest expense in this service, considering that the price of this enzyme is very expensive. Meanwhile, the process of making sago sugar takes a relatively long time, around 3 or 4 days. The use of the enzymes ?-amylase and ?-glucoamylase in the process of making sago starch into sago sugar among sago farmers in Meranti Islands Regency got good results in the form of understanding the manufacture and use of enzymes, providing enzyme packages to sago processing entrepreneurs, good sago sugar production results, and produce attractive packaging that can be profitable.